Multiplexes in India: Building Castles in a Low-income Market of Uneven Geographies - Gopalkrishnan, Sreeram (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The Indian film industry produces the highest number of movies in the world, in various languages, and casts a large shadow of influence on the socio-cultural landscape of the country. However, in terms of box-office value as a share of the total entertainment pie in India, films are a minor segment in a market with vast potential. The pandemic of 2020 drastically changed the fragile dynamics of the already-struggling film distribution and screening sector. Over the years, the Indian film business has staked its future on a business model forged around the “Mall-Multiplex” complex in a country that is mostly low-income or bottom of the pyramid (BoP). This exploratory article, with the help of existing data on theatre screen seats and high-potential population geographies, endeavours to understand India’s existing film entertainment business and sets out to spot the opportunities available for the low-priced film business as a value proposition.